Penerapan Terapi Afirmasi Positif dalam Meningkatkan Harga Diri pada Pasien Harga Diri Rendah : Studi Kasus - Febrinia Mutiara Fiska; Enggal Hadi Kurniyawan; Erti Ikhtiarini Dewi; Amalia Kusumaningsih (KHD Production, 2024)
Low self-esteem will experience negative feelings which cause loss of self-confidence, feelings of worthlessness and pessimism about oneself. Positive affirmation therapy is giving positive sentences which are usually about ideals and hopes expressed in thoughts or writing which are done repeatedly. This research aims to analyze how positive affirmation therapy is applied in providing mental nursing care for people with low self-esteem. The method used in this scientific work is a case study of a client in the Wijaya Kusuma room at Radjiman Wediodiningrat Lawang Hospital with a nursing problem of Chronic Low Self-Esteem adjusted to the Low Self-Esteem SP and then receiving additional non-pharmacological therapy in the form of positive affirmation therapy for 10 minutes at every 5-day meeting. Interventions for clients with chronic low self-esteem are adapted to SP chronic low self-esteem and self-esteem promotion interventions and substance abuse education. After that, Positive Affirmation therapy is given for 10 minutes at each meeting. This positive affirmation therapy can free oneself from negative thoughts and can increase an individual's ability to have positive thoughts. There is a need for non-pharmacological therapy that is easy, effective and economical, namely positive affirmation therapy to increase client self-esteem for clients in nursing care for clients with low self-esteem.